Frasa Nomina dan Fungsinya dalam Artikel Berita tentang Demonstrasi pada Detik.com Agustus 2025 - Anisah Hapsari; Aulia Destyana Maharani; Bella Septia Amalia Kahfi; Desvita Nindya Hardyani Putri; Ghadiva Luthfiyah Sahilyah; Asep Purwo Yudi Utomo; Qurrota Ayu Neina; Annisa Tetty Maharani (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
This study aims to describe the internal structure and syntactic functions of noun phrases in online news articles about demonstration actions published by Detik.com in August 2025. This research employs a qualitative descriptive approach, with observation and note-taking. Data were obtained from five news articles discussing demonstrations, then analyzed to identify the core elements (head) and modifiers, and to determine the syntactic functions of the phrases within sentences. The analysis results show that the most frequently encountered noun phrase pattern is Noun + Noun (N + N), with modifiers on the right that provide explanations of identity, location, or ownership. The most common syntactic function found is as the subject, followed by the object and adverbial of place. These findings confirm that noun phrases play an important role in explaining information and sentence structure in online news texts. Additionally, the use of noun phrases also reflects the media's language strategy in constructing social and political realities through concise, efficient, and information rich language.